PCR-RFLP assay as an option for primary HPV test - Golfetto, L. (Braz J Med Biol Res, 2018)
Persistent human papillomavirus (HPV) infection is an essential factor of cervical cancer. This study evaluated the analytical performance of restriction fragment length polymorphism polymerase chain reaction (PCR-RFLP) assay compared to PapilloCheck(®) microarray to identify human papilloma virus (HPV) in cervical cells. Three hundred and twenty-five women were analyzed. One sample was used for conventional cytology and another sample was collected using BD SurePath™ kit for HPV tests. Eighty samples (24.6%) were positive for HPV gene by PCR-Multiplex and were then submitted to PCR-RFLP and PapilloCheck(®) microarray. There was a genotyping agreement in 71.25% (57/80) on at least one HPV type between PCR-RFLP and PapilloCheck(®) microarray. In 22 samples (27.5%), the results were discordant and those samples were additionally analyzed by DNA sequencing. HPV 16 was the most prevalent HPV type found in both methods, followed by HPVs 53, 68, 18, 39, and 66 using PCR-RFLP analysis, and HPVs 39, 53, 68, 56, 31, and 66 using PapilloCheck(®) microarray. In the present study, a perfect agreement using Cohen's kappa (κ) was found in HPV 33 and 58 (κ=1), very good for HPV 51, and good for types 16, 18, 53, 59, 66, 68, 70, and 73. PCR-RFLP analysis identified only 25% (20/80) HPV coinfection, and PapilloCheck(®) microarray found 62.5% (50/80). Our Cohen's kappa results indicate that our in-house HPV genotyping testing (PCR-RFLP analysis) could be applied as a primary HPV test screening, especially in low income countries. If multiple HPV types are found in this primary test, a more descriptive test, such as PapilloCheck(®) microarray, could be performed.